THE INTEGRATION OF ISLAMIC COMMERCIAL AND SOCIAL ECONOMY THROUGH PRODUCTIVE WAQF TO PROMOTE PESANTREN WELFARE - Winarsih, Ratih; Masrifah, Atika Rukminastiti; Umam, Khoirul (Journal of Islamic Monetary Economics and Finance, 2019)
A pesantren (Islamic boarding school) as an Islamic educational institution basedon self-financing system has implemented waqf as a pillar of its development andbecome a potential waqf asset development. The productive waqf is considered asa key instrument for providing funds to actualizing its educational program. Sinceboth productive waqf and pesantren emphasize sustainability, and since productivewaqf can assist to support the process of education in pesantren, the study aims toinvestigate an integrated Islamic social and commercial economy model applicable inpesantren. This will ensure utilization of the combined resources of productive waqfand pesantren in promoting pesantren welfare. The study focuses on 263 operationalchief, assatidz or teacher, musyrif, musyrifah or santri companion and santri or studentsin Pesantren in Java and Sumatra using. Structural Equation Modeling (SEM) adoptedto examine the relationship among the five constructs i.e., productive waqf, businessunit, project financing, human resource and pesantren welfare. While the reliabilityand validity are established, the structural relationship between the constructs revealsthat the integrated model has a strong relationship with the pesantren welfare inmany ways. In relation with business unit and profitable commercial activities, humanresources have its significant role to assist pesantren tries its level best to realizedeveloped productive waqf. Specifically, the result shows all five constructs havesignificant impact in promoting pesantren welfare, which suggests that the model aswell as the instrument should be further implemented in pesantren.